Overview of Knowledge of Pregnant Women About the Dangers of HIV/AIDS at the Pratama Nusantara Clinic Mandau District Bengkalis Regency in 2019 - Jumiati,; Diana Novita , (JIM - Journal International Multidisciplinary, 2023)
HIV/AIDS is a relatively well-known disease with many health problems, especially when it occurs in pregnant women. Dangers that can occur such as immune system disorders and pregnant women are susceptible to infection, pregnancy will fight the progress of HIV infection, conversely the effects of HIV in pregnancy are intra uterine growth retardation and low birth weight, as well as increased preterm birth and the baby can also be infected in the womb. HIV continues to be a major problem in the world, so far it has claimed more than 35 million lives. At the end of 2017, there were around 36.5 million people living with HIV and 1.8 million people newly infected with HIV worldwide. About 59% of adults and 52% of children with HIV are on lifelong antiretroviral therapy (ART). The high coverage of ART in the world for pregnant and lactating women is 80%. This study aims to describe the knowledge of pregnant women about the dangers of HIV/AIDS at the Pratama Nusantara Clinic, Mandau District, Bengkalis Regency in 2019. The research design used is descriptive quantitative. The research was conducted from June 1 to June 20 2019. The population in this study consisted of 38 pregnant women with a sample of 35 people using Simple Random Sampling. Data were obtained from primary and secondary data for further analysis of the data univariately. The results showed that the majority of pregnant women lacked knowledge about the dangers of HIV/AIDS as many as 18 people (51.43%), at the age of 20-35 years as many as 10 people (28.57%), high school education level as many as 8 people (22.86 %) %), and 7 people (20%) got information about the dangers of HIV/AIDS through electronic media. It is expected that pregnant women will further increase their knowledge by adding information from various media and more often participate in counseling programs conducted by health workers/facilities and participate in carrying out HIV/AIDS testing during pregnancy.